2021
DOI: 10.3390/healthcare9040472
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Interventions to Support Self-Management in Stroke Survivors: A Systematic Review

Abstract: Telehealth (TH) intervention is a method to optimize self-management (SM) support in stroke survivors. Objectives of this study included identifying the TH-SM intervention’s focus and SM support components, the TH delivery type, and the TH-SM support effects on stroke survivors. Five databases were searched for the years 2005–2020 to identify TH-SM support interventions for stroke survivors. Randomized controlled trials and quasi-experimental, one-group re-post study designs were included. Ten studies were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…PWNDs are assessed and treated in their actual living environment, which is highly encouraging for the patients. It also reduces the service cost, and it cuts down the cost of traveling to access rehabilitation ( 23 , 24 ). Therapeutic progress is currently being well-documented because of the auto-digitization features of telecommunication technology ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PWNDs are assessed and treated in their actual living environment, which is highly encouraging for the patients. It also reduces the service cost, and it cuts down the cost of traveling to access rehabilitation ( 23 , 24 ). Therapeutic progress is currently being well-documented because of the auto-digitization features of telecommunication technology ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also reduces the service cost, and it cuts down the cost of traveling to access rehabilitation ( 23 , 24 ). Therapeutic progress is currently being well-documented because of the auto-digitization features of telecommunication technology ( 23 , 24 ). Overall, access to rehabilitation has improved with the introduction of TNR services.…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to determine how best to incorporate telehealth modalities into routine clinical practice for delivery of stroke follow-up care. 16 Our research raises several important questions that require further investigation. We experienced challenges with recruitment and retention.…”
Section: Discussionmentioning
confidence: 95%
“…38 Our results parallel existing evidence from the systematic review reporting positive effects of the telemedicine SMS interventions on all self-efficacy outcomes. 16 However, it is important to point out that the telehealth delivery type most used in selected studies was messaging.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that a combination of selfmanagement and telehealth could offer promising interventions (Saragih et al, 2021). Telehealth applications can be particularly helpful for messaging, telephone, video conferencing, and online platforms and these are very applicable for patients at home otherwise limited by time and distance (Anderson et al, 2022;Hwang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%